Il metodo didattico di Stanislao Cannizzaro - Zingales, Roberto (Chimica nella Scuola, 2023)
By analysing some Stanislao Cannizzaro’s papers and conference texts, it can be shown the way in which he taught atomic theory, which he considered the turning point in XIX century Chemistry.